Czy Leon Petrażycki był socjologiem? - Kojder, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The question posed in the title of the article is a rhetorical question, especially for people who know the creativity and life of Leon Petrażycki. It cannot be denied that Petrazycki’s place in the science of sociology is more than insignificant. One of the reasons is probably that Petrażycki strongly rejected the traditional concept of sociology as „social science”, which aims to describe and explain all „social phenomena”. He thought that „sociology represents something like a museum of scientific pathology”. Nevertheless, Petrażycki, dealing with intersubjective, social forms of law, treated these problems sociologically, with the ingenuity of a first-rate sociologist, he analyzed the social conditions of law, and on the other hand - the impact of law on social life. Attempt to change the attitude of sociology and to rebuild its methodological made by Petrażycki did not meet with wider interest. The main reason for this was that the work on sociology intended already in 1907 could not be completed and published in the following years. His vision of sociology, therefore, remained virtually unknown. In this article, are presented main scientific interests of Petrażycki, as well as the approach to various scientific issues which he undertook. The presented description of his scientific activity and analysis of some of the preserved works that were not destroyed during World War II allow us to reconstruct the main theses of the sociology he created and practiced. The main conclusion of the study is that based on the information available, Petrazycki’s concept belongs to the evolutionary sociological trend. Darwinism should be regarded as its main source of inspiration, because the author of “Theory of Law and State” was mainly interested in the processes of adapting the human psyche to the conditions of collective life and co-creating these conditions in the process of emotional and intellectual contagion.